MATLAB numerical methods with chemical engineering applications - Al-Malah, Kamal I. M. (New York : McGraw-Hill, 2013)
'A practical, professional guide to MATLAB applications, numerical techniques, and scientific computing. MATLAB Numerical Methods with Chemical Engineering Applications shows how to use MATLAB to model and simulate physical problems in the chemical engineering realm. This cookbook-style guide allows quick mastery of this important, powerful computational tool for engineers. Recipe-style presentation with every step needed toward the final solution algorithmically explained via MATLAB snapshots in parallel with the text. Concise explanations of essential MATLAB commands, programming features, graphical capabilities, and desktop interface. Written for MATLAB 7.11 (R2011a); can also be used with earlier (and later) versions of MATLAB. Each chapter is a standalone entity covering a computational skill needed by engineers. Includes end-of-chapter problems'--
'A practical, professional guide to MATLAB applications, numerical techniques, and scientific computing'--
Includes index.
Keywords: MATLAB; Chemical engineering -- Data processing